تحقيق مخطوطات النوازل الفقهية الشنقيطية, بيان لأهم الصعوبات, النوازل الأعمشية أنموذجا - جراية, عماد; حواس, الهادي (جامعة الوادي - University of Eloued, 2022)
ملخص: تعد بلاد شنقيط -موريتانيا- من أكبر الحواضر العلمية الإسلامية؛ فقد زخرت هذه البلاد بعلماء استطاعوا أن يسايروا الواقع بخدمة الدين, والحفاظ على التراث في وقت واحد. فكان من أبرز المشتغلين بالفقه العملي التنزيلي إمامهم المقدم ابن الأعمش العلوي الشنقيطي. كان المرجع في الفتوى والنوازل في زمانه؛ حيث جُمعَت له نوازل سمِّيت بالنوازل الأعمشية. وهي كتاب مخطوط قمت بتحقيقه في رسالة دكتوراه. فأردنا أن نضع خلاصة هذه التجربة في مقال علمي نبين فيه ما تنفرد به مخطوطات النوازل الفقهية الشنقيطية عن غيرها من المخطوطات؛ من جهة الصعوبات التي تواجه المحققين. فجاء المقال موسوما بـ:" تَحْقِيقُ مَخْطُوطَاتِ النَّوَازِلِ الفِقْهِيَّةِ الشِنْقِيطِيَّةِ, بَيَانٌ لِأَهَمِّ الصُّعُوبَاتِ, النَوَازِلُ الأَعْمَشِيَّةُ – أُنْمُوذَجًا - . Abstract : The country of Chinguetti - Mauritania - is one of the largest Islamic scientific cities; This country abounded with scholars who were able to keep pace with reality by serving religion, and preserving heritage at the same time. He was one of the most prominent practitioners of practical fiqh al-Tawzli, their imam, al-Muqaddam Ibn al-A'mash al-'Alawi al-Shanqeeti. He was the reference in the fatwa and calamities of his time; Where he collected cataracts called paraseptal cataracts. It is a manuscript book that I achieved in my PhD thesis. We wanted to put the summary of this experience in a scientific article in which we show what is unique to the manuscripts of the Shanqeeqite jurisprudential calamities from other manuscripts. On the one hand, the difficulties faced by investigators. The article is tagged with: Investigating the manuscripts of the schizophrenia jurisprudence A statement of the most important difficulties Paraventricular progenitors - model -
مقال
Keywords: تحقيق مخطوطات؛ النوازل الفقهية؛ الصعوبات؛ النوازل الأعمشية.; Keywords: manuscript investigation; jurisprudential calamities; difficulties; Gastrointestinal cataracts